A Pilot Telerehabilitation Program: Delivering Early Intervention Services to Rural Families - Jana Cason (International Journal of Telerehabilitation)
The enTECH Telerehabilitation Program explored the use of telerehabilitation as an alternative service delivery model for early intervention therapy services. Utilizing the Kentucky Telehealth Network, two families living in rural Kentucky received occupational therapy services over a 12-week period. Following program implementation, qualitative data was collected using participant journals and interviews. Data analysis identified three thematic categories related to the program: benefits/strengths, challenges/weaknesses, and recommendations for program improvement. Results of the program evaluation indicated that telerehabilitation has the potential to cost-effectively meet the therapeutic needs of children living in rural areas where provider shortages exist. The enTECH Telerehabilitation Program serves as a model for how telerehabilitation can be used to deliver early intervention services to ameliorate health disparities and improve access to rehabilitation services. Keywords: Telerehabilitation, Occupational Therapy, Rural, Early Intervention, Children, Program Evaluation, Cost Analysis